1994
DOI: 10.1038/bjc.1994.16
|View full text |Cite
|
Sign up to set email alerts
|

Duck hepatitis B virus infection, aflatoxin B1 and liver cancer in domestic Chinese ducks

Abstract: The oncogenicity of Duck hepatitis B virus (DHBV) is unclear since hepatocellular carcinomas (HCCs) have been reported only in domestic ducks in Qidong, an area of China where hepatitis B virus (HBV) and aflatoxin B1 (AFB1) are risk factors for liver cancer in man. In order to better define the association between DHBV infection, AFB1 and HCC we analysed a series of 16 duck liver samples collected from local farms in Qidong. HCC was found in eight and cirrhosis in one of these samples. Furthermore bile duct pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…In the present investigation, the data from the results demonstrated that dietary aflatoxin significantly lowers the feed intake and body weight of the birds. Similar results has been reported by Cova et al (1994). Sell et al (1998), studying ducks, had similarly reported decreased feed intake and lower body weight.…”
Section: Resultssupporting
confidence: 80%
“…In the present investigation, the data from the results demonstrated that dietary aflatoxin significantly lowers the feed intake and body weight of the birds. Similar results has been reported by Cova et al (1994). Sell et al (1998), studying ducks, had similarly reported decreased feed intake and lower body weight.…”
Section: Resultssupporting
confidence: 80%
“…Periportal cell proliferation is a well-documented response of the duck liver to injury by the hepatotoxin, aflatoxin B 1 . [18][19][20] At day 9, the bile ductulelike cells were organized into cords and ductular networks that had greatly regressed in their prominence by 23 days' postinfection. It is possible that these small cells contributed to the restoration of normal hepatic architecture observed by day 23 postinfection by providing a source of newly differentiated hepatocytes to the injured liver.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DNA was extracted from DHBV positive duck serum and used as control for input viral DNA migration. The DNAs (5 mg) were analyzed by Southern blot using a 32 P-labelled DHBV probe as described previously [38,39]. Viral DNA was quantified by PhosphorImager using ImageQuant software (Molecular Dynamics).…”
Section: Analysis Of Viral Dnamentioning
confidence: 99%